Antidiabetic Drug Alogliptin Protects the Heart Against Ischemia-reperfusion Injury Through GLP-1 Receptor-dependent and Receptor-independent Pathways Involving Nitric Oxide Production in Rabbits. Issue 6 (December 2017) - Baba, Shinya; Iwasa, Masamitsu; Higashi, Kenshi; Minatoguchi, Shingo; Yamada, Yoshihisa; Kanamori, Hiromitsu; Kawasaki, Masanori; Nishigaki, Kazuhiko; Minatoguchi, Shinya
Abstract : Abstract: GLP-1 has been reported to be cardioprotective against ischemia-reperfusion injury. We aimed to examine the effect of alogliptin, which may produce GLP-1, on ischemia-reperfusion injury and its mechanisms. Rabbits were fed a normal chow (control group) and a chow containing alogliptin (2 mg·kg −1 ·d −1 : alogliptin-L group and 20 mg·kg −1 ·d −1 : alogliptin-H group) for 7 days. The rabbits underwent 30 minutes of coronary occlusion and 48 hours of reperfusion. Exendin (9–39) [5 or 50 μg/kg, i.v., alogliptin-H+exendin (9–39)-L group and alogliptin-H+exendin (9–39)-H group] or L-NAME (10 mg/kg, i.v., alogliptin-H+L-NAME group) was administered to the alogliptin-H group. Alogliptin dose-dependently reduced the infarct size, which was partially blocked by exendin (9–39), but completely blocked by L-NAME. Exendin (9–39) or L-NAME alone did not affect the infarct size for themselves. The left ventricular ejection fraction and ±dP/dt were higher in the alogliptin-L group and alogliptin-H group than in the control group. Alogliptin increased the serum NOx and plasma GLP-1 levels, and those levels inversely correlated with the infarct size. Alogliptin upregulated the expressions of phosphorylated (p)-Akt and p-eNOS, which were inhibited by exendin (9–39) and L-NAME, respectively. In conclusion, alogliptin protects the heart against ischemia-reperfusion injury through GLP-1 receptor-dependent and receptor-independent pathways which involve nitric oxide production in rabbits.